2003
DOI: 10.1113/jphysiol.2003.044701
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression patterns during disuse atrophy in rat skeletal muscle

Abstract: Muscular inactivity leads to atrophy, weakness, and decreased fatigue resistance. In order to provide a window into the dynamic processes that underlie muscle atrophy, we performed global gene expression analysis of rat soleus muscles using Affymetrix GeneChips at 1, 4, 7 and 14 days of hindlimb unloading. Expression of 309 known genes was significantly changed by at least 2-fold (212 upregulated, 97 downregulated). K-means clustering was used to divide these genes into co-regulated clusters based on the simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
90
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(109 citation statements)
references
References 76 publications
17
90
1
1
Order By: Relevance
“…Our finding that endogenous Hsp70 is significantly decreased in the young, adult animals after 6 days of disuse is in agreement with previous studies using an immobilization model (Stevenson et al 2003;Selsby and Dodd 2005;Lawler et al 2006;Selsby et al 2007;Senf et al 2008). In addition, the immobilization-induced decreased Hsp70 in the senescent animals has not been demonstrated but is not surprising.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that endogenous Hsp70 is significantly decreased in the young, adult animals after 6 days of disuse is in agreement with previous studies using an immobilization model (Stevenson et al 2003;Selsby and Dodd 2005;Lawler et al 2006;Selsby et al 2007;Senf et al 2008). In addition, the immobilization-induced decreased Hsp70 in the senescent animals has not been demonstrated but is not surprising.…”
Section: Discussionsupporting
confidence: 93%
“…Previously we, and others, have shown increased Nedd4-1 expression in gastrocnemius muscles undergoing denervation or unloading induced atrophy [15], [16], [30]. To confirm this phenomenon in our genetic mouse model, Nedd4-1 SMS-KO and littermate Myo Cre ;Nedd4-1 +/+ control mice underwent right tibial nerve transection with the left hind limb serving as control.…”
Section: Resultssupporting
confidence: 73%
“…We have demonstrated that during hibernation the 13-lined ground squirrel activates PGC-1α signaling in ways that are very similar to endurance exercise. Previous studies in rats have shown that hindlimb immobilization or muscle unloading is associated with a slow-to-fast fiber type transformation, resulting in a muscle profile more susceptible to fatigue (Fitts, et al, 2001, Stevenson, et al, 2003, Thorlund, et al, 2011). In contrast, we demonstrate that hibernating skeletal muscle exhibits a fiber type switch towards slow Type I muscle fibers and a concomitant decrease in fast Type IIB fibers.…”
Section: Discussionmentioning
confidence: 99%